A comparative analysis of covered distance in top footballers in final matches on last three world cups - Ademovic, A. (Sportski Logos, 2019)
This research is a transversal study with the goal of determining the covered distances in top footballers in final matches of the last three world cups. The research was conducted with 50 top footballers, aged 19 to 35, who played all ninety minutes of final matches. The respondents are divided into three groups. The first group consists of players of national teams of Spain and the Netherlands, finalists of the 2010 World Cup played in South Africa (n=18). The second group consists of players of national teams of Germany and Argentina, finalists of the 2014 World Cup in Brazil (n=17). The third group consists of players of national teams of Croatia and France, finalists of the 2018 World Cup in Russia (n=15). The acquired results show that the highest total average covered distance and highest covered distance in the first and the second halftime was realized in the final match of the 2014 World Cup. The results of the univariant analysis of the ANOVA variant showed that significant statistical distinction was achieved (on the level of P=0.001) in the variable of covered distance in the first halftime (SEPRDPP), whereas other variables did not show significant statistical differences.